International Workshop on Dynamic Behaviour of Structures and Materials, Interaction and Friction Across the Strain Rates - 2015, PETER (Engineering Transactions, 2015)
The workshop will cover both theoretical modelling of the mechanical behavior of materials and structures under dynamic loading and all aspects related to friction and contact. There will be eight main themes: 1. Constitutive relations and modelling 2. Numerical simulations 3. Perforation and Impact 4. Crashworthiness 5. Experiments and inverse methods 6. Friction and interaction 7. Surface and contact 8. Shock and Blast Loading